Effects of X-Rays on Children's Health and Development - Berri, Amjad Raad; Kazem, Atheer Jawad; fahd, Laith Bassim Abed; Abdullah, Khalid Abdulsattar; Ahmed, Ahmed Ali (American Journal of Botany and Bioengineering, 2025)
Since their discovery, X-rays have played a vital role in medical diagnostics; however, their effects on children’s health and development remain a matter of serious concern. Despite wide clinical use, there is still a significant knowledge gap regarding dose optimization, cumulative effects, and long-term risks for pediatric patients. This article systematically reviews the biological mechanisms of X-ray interaction with children's developing tissues, the risks of acute and chronic health effects, and the limitations of current pediatric radiology practices. Based on a review of 14 studies and multiple clinical cases, the findings show that children are highly radiosensitive, with increased risks of leukemia, thyroid cancer, and developmental abnormalities even at low-dose exposures. Results emphasize the urgent need for applying ALARA principles, refining pediatric imaging protocols, and improving parental and practitioner awareness. This study underlines the necessity of international guidelines and innovative imaging alternatives to minimize unnecessary radiation exposure in children.